The speed of motor response and its relationship to the accuracy of defensive skills performance by the libero in volleyball for Wasit club players - Shrad, Muhammad Ghaeib; Hamza, Hamza Tariq; Amir, Ammar Nasr Abdul (Sulaimani Journal for Humanities, 2026)
The progress of players in any sport and their ability to fulfill the required motor duties depends on the extent to which they possess those physical attributes. Otherwise, no individual can master the basic skills of the sport they specialize in if they lack some of the necessary attributes for that particular sport, especially in a game like volleyball. Researchers, due to their close involvement with this game, have observed a significant problem: the weakness of libero players in certain defensive skills, which manifests as a slowness in reaching the right place at the right time. This, in turn, leads to team confusion and consequently the loss of points, which is inconsistent with the development of the game at present. It was therefore necessary to determine the relationship between motor response speed and the accuracy of defensive skills performed by the libero in volleyball. Given the nature of the problem, a descriptive approach was adopted, as it was best suited to the research question. The research population consisted of 50 volleyball players in Wasit Governorate during the 2024-2025 season. The sample comprised 13 libero players, divided into a pilot study of 3 players and a main study of 10 players, representing 26% of the research population. After considerable effort, the researchers arrived at the following conclusions: 1- A significant correlation was found between motor response speed and the skill of receiving the serve. 3- A stronger correlation was found between court defense skills and the skill of receiving the serve. The researchers also offered several recommendations, including: 1- Emphasizing the variable of motor response speed, which has a direct impact on the skill performance of defensive skills in volleyball for the libero. 2. Emphasize defensive skills and utilize the rule changes in volleyball. 3. Focus on specific exercises to develop the quick reflexes of the libero in volleyball. 4. Provide the libero with sufficient time to develop their defensive skills in line with the evolving offensive techniques in volleyball.